Evaluation of the Pacific Financial Technical Assistance Centre. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This report presents the analysis, findings, conclusions and recommendations of the evaluation of the Pacific Financial Technical Assistance Center (PFTAC) that was undertaken between April 26 and May 14, 2004.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet